Two birds, one stone: can Nigeria have the best of both worlds internationally while chasing regional leadership? - Radu Magdin (Frontiers in Political Science)
The main aim of the paper is to analyze how Nigeria is navigating local West African ambitions while playing a more determined role in international politics. The changes in the global dynamics offer Nigeria an unexpected opportunity to choose how to play its foreign policy game onward. On the one hand, there is a long-lasting relationship with the Western nations, particularly with the United States. On the other hand, BRICS’s newly regained vitality appeals to the African country as an alternative to having more ownership of the important decisions involving itself, the region and even international politics. In this context, the main question that arises is if Nigeria is on the path to choose one of the two ideological-economic blocks already mentioned or if is it able to elegantly balance between them to pursue its national and regional interests while getting the best of both worlds.